2021
DOI: 10.1002/acn3.51463
|View full text |Cite
|
Sign up to set email alerts
|

Lack of progression of beta dynamics after long‐term subthalamic neurostimulation

Abstract: Objective: To investigate the progression of neural and motor features of Parkinson's disease in a longitudinal study, after washout of medication and bilateral subthalamic nucleus deep brain stimulation (STN DBS). Methods: Participants with clinically established Parkinson's disease underwent bilateral implantation of DBS leads (18 participants, 13 male) within the STN using standard functional frameless stereotactic technique and multi-pass microelectrode recording. Both DBS leads were connected to an implan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 53 publications
6
19
0
Order By: Relevance
“…In contrast to the observed increase in bilateral STN coherence over time, neither STN beta power or beta burst duration significantly changed over time, and neither were related to the observed worsening of bradykinesia. This replicates a previous finding from our lab where neither beta power or burst duration, as measured at rest, showed significant increases over three years 22 . The lack of increase in beta power within the STN implies that the observed increase in beta coherence over time is not a byproduct of changes in power, but rather evidence for a change in synchrony between the two STNs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to the observed increase in bilateral STN coherence over time, neither STN beta power or beta burst duration significantly changed over time, and neither were related to the observed worsening of bradykinesia. This replicates a previous finding from our lab where neither beta power or burst duration, as measured at rest, showed significant increases over three years 22 . The lack of increase in beta power within the STN implies that the observed increase in beta coherence over time is not a byproduct of changes in power, but rather evidence for a change in synchrony between the two STNs.…”
Section: Discussionsupporting
confidence: 92%
“…The advent of chronically implanted sensing neurostimulators has enabled the ability to track subcortical basal ganglia dynamics longitudinally alongside potential disease progression. Interestingly, the largest multi-year longitudinal LFP study in PD to date found that STN beta bursts and beta power measured at rest were stable over time and no worsening of overall clinical motor impairment was observed 22 . However, when examining symptom-specific changes over time, there is evidence that bradykinesia and axial symptoms may continue to worsen with chronic STN DBS 23,24 , compared to tremor, which improves over time 25,26 .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mean age of the participants was 60.2 ± 6.2 years (mean ± SD) with a mean disease duration of 10.6 ± 3.8 years (see Table 1 for further details). Previous studies confirmed stability of beta-band activity for at least 5 years 34 , 45 and correlation between disease duration and beta-band suppression at stimulation intensities for the best clinical effect was not significant. The mean pre-operative OFF medication UPDRS-III score was 50.9 ± 10.4.…”
Section: Methodsmentioning
confidence: 67%
“…3c , there is no consistent suppression of low-frequency activity across STNs. Overall, beta-band activity seems to be a more stable biomarker for chronic sensing enabled devices such as Percept that use a 5 Hz bin frequency band for the feedback signal 34 .…”
Section: Discussionmentioning
confidence: 97%